Motyw Kobiety-Góry we współczesnych islandzkich filmach i serialach - Adamski, Tomasz (Strategie komunikacyjne i procesy twórcze, 2022)
The author begins his article with a description of the Icelandic landscape, with particular emphasis on volcanoes. This is the starting point for an outline of the mother (femininity) figure in Icelandic culture, which has been used to emphasize Iceland's independence and statehood. This figure was called the Mountain Woman and became an allegorical personification of the motherland for Icelanders. Over the years, she gained a bodily dimension (Fjallkonan) and her image was very often used in Icelandic art and poetry. References to this symbol also appeared in an Icelandic film or tv series, if only because nature was encoded as clearly feminine. The ideal woman is often depicted in Icelandic cultural texts as a person untainted by the evil of civilization and living in harmony with nature. The frequent identification of this mythical character with Iceland itself can be seen in contemporary Icelandic films and series such as: The Cliff, Rams. An Icelandic tale or 101 Reykjavik. The Mountain Woman can also be read as a prototype for the figure of strong women present in many contemporary Icelandic productions, to mention only: Valhalla Murders or The Woman at War.